Illuminating Polysulfide Distribution in Lithium Sulfur Batteries; Tracking Polysulfide Shuttle Using Operando Optical Fluorescence Microscopy - Coke, K; Johnson, MJ; Robinson, JB; Rettie, AJE; Miller, TS; Shearing, PR (American Chemical Society, 2024)
High-energy-density lithium sulfur (Li–S) batteries suffer heavily from the polysulfide shuttle effect, a result of the dissolution and transport of intermediate polysulfides from the cathode, into the electrolyte, and onto the anode, leading to rapid cell degradation. If this primary mechanism of cell failure is to be overcome, the distribution, dynamics, and degree of polysulfide transport must first be understood in depth. In this work, operando optical fluorescence microscope imaging of optically accessible Li–S cells is shown to enable real-time qualitative visualization of the spatial distribution of lithium polysulfides, both within the electrolyte and porous cathode. Quantitative determinations of spatial concentration are also possible at a low enough concentration. The distribution throughout cycling is monitored, including direct observation of polysulfide shuttling to the anode and consequent dendrite formation. This was enabled through the optimization of a selective fluorescent dye, verified to fluoresce proportionally with concentration of polysulfides within Li–S cells. This ability to directly and conveniently track the spatial distribution of soluble polysulfide intermediates in Li–S battery electrolytes, while the cell operates, has the potential to have a widespread impact across the field, for example, by enabling the influence of a variety of polysulfide mitigation strategies to be assessed and optimized, including in this work the LiNO3 additive.